2017
DOI: 10.1158/1541-7786.mcr-16-0373
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Decreases HBx-Induced Phospho-Akt in Hepatocytes via P2X Receptors

Abstract: Hepatocellular carcinoma (HCC) is rated as the fifth most common malignancy and third in cancer-related deaths worldwide. Statins, HMG-CoA reductase inhibitors, are potent cholesterol-lowering drugs, and recent epidemiologic evidence suggests that statins prevent aggressive HCC development. Previous experiments revealed that statins downregulate phosphorylated Akt (pAkt). Here, it is demonstrated that atorvastatin decreases nuclear pAkt levels in pancreatic and lung cancer cell lines within minutes, and this r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Evidence has emerged to indicate that increased lipids and cholesterol, which are correlated with elevated oncogenic growth signaling, such as PI3K-AKT and MAPK signaling in cancer cells, are now considered a hallmark of cancer aggressiveness [ 14 , 20 ]. Indeed, many reports have shown that cholesterol-lowering drugs, such as atorvastatin, lovastatin, and simvastatin, inhibit cancer cell growth and invasiveness via the suppression of oncogenic signaling in HCC, melanoma, glioma, and ovarian cancer [ 21 , 22 , 23 , 24 ]. On this basis, the inhibitory effect of emodin on oncogenic growth signaling in HCC cells was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence has emerged to indicate that increased lipids and cholesterol, which are correlated with elevated oncogenic growth signaling, such as PI3K-AKT and MAPK signaling in cancer cells, are now considered a hallmark of cancer aggressiveness [ 14 , 20 ]. Indeed, many reports have shown that cholesterol-lowering drugs, such as atorvastatin, lovastatin, and simvastatin, inhibit cancer cell growth and invasiveness via the suppression of oncogenic signaling in HCC, melanoma, glioma, and ovarian cancer [ 21 , 22 , 23 , 24 ]. On this basis, the inhibitory effect of emodin on oncogenic growth signaling in HCC cells was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…In experimental systems, statins elicit a variety of pleotropic anti-neoplastic, in addition to cholesterol-lowering, effects. Statins inhibit oncogenic pathways, including Myc, 156 Akt, 157,158 integrin and Rho-dependent kinase, 159 nuclear factor κB (NF-κB), and tumor necrosis factor (TNF)-mediated IL6 production, 160 and Hippo pathway effector TAZ, and extracellular signal–regulated kinase 1/2 (ERK1/2), 161 whereas adenosine monophosphate-activated protein kinase (AMPK) and p38/mitogen-activated protein kinase (MAPK) pathways are activated,. 162,163 and p53-dependent apoptosis is induced 164 (Figure 3).…”
Section: Etiology-specific Hcc Preventionmentioning
confidence: 99%
“…Moreover, in vivo studies showed promising results in antitumor effects such as the inhibition of cell proliferation and the promotion of tumor cell differentiation in various animal models [17,18]. Statins perhaps help to prevent HCC by suppressing oncogenic pathways including Rho-dependent kinase [19], tumor necrosis factor (TNF)-mediated interleukin (IL6) production [20], Akt [21], Myc-medicated cell proliferation, and so on [22] (Figure 1). The beneficial effects of statin use have ubiquitously been reported for liver cancer patients.…”
Section: Introductionmentioning
confidence: 99%